Estimating the reduction in single-occupancy vehicles entering Kuala Lumpur as a result of telecommuting by female employees - Jaff, Mootaz M.; Kadar Hamsa, Abdul Azeez; Ibrahim, Mansor; Mohamed, Mohd Zin; Zahari, Rustam Khairi (2015)
A number of Malaysian cities are experiencing severe transport problems resulting from rapidly increasing vehicle ownership and usage, and the insufficient supply and inferior quality of public transportation. The trend of congestion, frequent traffic accidents and air pollution is nowhere more prevalent than in Kuala Lumpur where telecommuting is increasingly being perceived as a viable travel demand management strategy. Due to a number of travel patterns and characteristics that are unique to female commuters and the relatively large participation rate of women in the Malaysian work force, telecommuting by women workers seems a more relevant and potentially more crucial means of alleviating rush hour traffic in the Kuala Lumpur metropolitan area. The aim of this study is to estimate both the potential and actual reduction in single-occupancy vehicles entering the city of Kuala Lumpur during peak hours as a result of involving female employees in the practice of telecommuting.